Analysis Of Differences In The Quality Of Galamai Using Brown Sugar And Palm Sugar - Rizki, Muhammad; Elida, Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
The study aimed to analyze differences in galamai quality using cane and palm brown sugar which includes shape, color, aroma, texture and taste. The type of research used is a pure experiment with quantitative methods, namely conducting direct experiments on the manufacture of galamai using sugarcane and palm brown sugar. This research was conducted at Tata Boga Workshop on August 30 - September 30, 2021. This study used a type of Complete Random Design (RAL) with 3 repetitions. The data used is primary data obtained directly from 5 expert panelists who provide answers on organoleptic test formats to galamai quality using sugar cane and aren brown sugar. The data obtained is tabulated into table form and analyzed to see the difference between the two treatments using the t test. The results showed that the average value did not have a significant difference in X1 and X2 treatment of the quality of the galamai that stated H0 was received, namely the quality of shapes (rectangular size) 3.33 and 3.20; (neat) shapes 3.53 and 3.33; (uniform) forms 3,27 and 3.20; (average) shapes 3,33 and 3.20; galamai colors 3.80 and 3.73; colors (shiny) 3.87 and 3.80; aromas 3.87 and 3.80; texture (chewy) 3.73 and 3.80; texture (slippery) 3.80 and 3.87; tastes 3.73 and 3.80. Overall with the average tabulation of the best results data from both variables is found in galamai using cane brown sugar (X1).